PENGARUH GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK MUHAMMADIYAH 2 PALERAN - Iwanda Fatma Sari; Sofyan Rofi; Bahar Agus Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Islamic Religious Education (PAI) Teacher's Role on Students' Learning Motivation at SMK Muhammadiyah 2 Paleran. The research employed a quantitative descriptive approach using simple linear regression analysis. The research population consisted of 68 students in grade XI from three vocational programs: Software Engineering, Motorcycle Engineering, and Digital Business. Data were collected through questionnaires using a five-point Likert scale, supplemented by observation and documentation. Instrument validity was tested using Pearson Product Moment correlation and reliability using Cronbach's Alpha. Prerequisite tests included the Kolmogorov-Smirnov normality test and the Test of Linearity. The results of data analysis yielded the regression equation Y = 32.596 + 0.549X. The partial t-test obtained a t-count of 8.268 with a significance value of 0.000 < 0.05, indicating that the PAI Teacher's Role variable has a positive and significant effect on Students' Learning Motivation. The coefficient of determination (R Square) of 0.509 reveals that the PAI Teacher's Role accounts for 50.9% of the variance in Students' Learning Motivation, while the remaining 49.1% is influenced by other factors outside this study. Keywords: Teacher's Role PAI, Learning Motivation, Simple Linear Regression This study aims to determine the effect of the Islamic Religious Education (PAI) Teacher's Role on Students' Learning Motivation at SMK Muhammadiyah 2 Paleran. The research employed a quantitative descriptive approach using simple linear regression analysis. The research population consisted of 68 students in grade XI from three vocational programs: Software Engineering, Motorcycle Engineering, and Digital Business. Data were collected through questionnaires using a five-point Likert scale, supplemented by observation and documentation. Instrument validity was tested using Pearson Product Moment correlation and reliability using Cronbach's Alpha. Prerequisite tests included the Kolmogorov-Smirnov normality test and the Test of Linearity. The results of data analysis yielded the regression equation Y = 32.596 + 0.549X. The partial t-test obtained a t-count of 8.268 with a significance value of 0.000 < 0.05, indicating that the PAI Teacher's Role variable has a positive and significant effect on Students' Learning Motivation. The coefficient of determination (R Square) of 0.509 reveals that the PAI Teacher's Role accounts for 50.9% of the variance in Students' Learning Motivation, while the remaining 49.1% is influenced by other factors outside this study. Keywords: Teacher's Role PAI, Learning Motivation, Simple Linear Regression